Diagnostic values of DAS28 and DAS28-squeeze in evaluating Rheumatoid Arthritis disease - David Santosa; Rudy Hidayat; Marcel Prasetyo; Pringgodigdo Nugroho (Indonesian Journal of Rheumatology, 2016)
Background : In recent years, rheumatoid arthritis (RA) uses a â€œtreat to targetâ€Â  treatment strategy. This strategy requires a valid and accurate tool for assessing disease activity. The most widely used tool is DAS28, which was developed from DAS with the omission of ankle and foot joints. There has been many critization aboutthe accuracy of DAS28 in classifying the state of RA disease. Most importantly, when an active disease state was misclassified as an inactive state (false negative)which lead to under treat and subsequently to disability. The difference between DAS28 and DAS lies mainly in the exclusion of ankle and foot joints, thus DAS28-squeeze, a new and simple tool has been proposed. It comprises the same 28 joints in DAS28 added with a sqeeze test on both metatarsophalangeal joints. However, this new tool has never been validated with any imaging techniques.Objective : To assess the diagnostic values of DAS28 and DAS28-squeeze.Methods : This study comprised a cross-sectional diagnostic study, using Power Doppler sonography as a standard reference in evaluating the diagnostic value ofDAS28 and DAS28-squeeze. This study uses the most sringent sonography criteria of active disease which is an active Doppler signal with a moderate synovial hypertrophy on B-mode. Results : Over the study period, 56 subjects underwent diagnostic tests using DAS28, DAS28-squeeze and Power Doppler sonography. There were 4 false negativecases in DAS28 and 1 case in DAS28-squeeze. The sensitivities of DAS28 and DAS28-squeeze to identify active disease using Power Doppler sonography as reference standard were 73.3% (95%CI Â± 11.59) and 93.3% (95%CI Â± 6.55), respectively. While the specificities of DAS28 and DAS28-squeeze were 36.6% (95%CI Â± 12.62) and 34.1% (95%CI Â± 12.42), respectively. Furthermore the negative likelihood ratioof DAS28 and DAS28-squeeze were 0.73 and 0.19, respectively.Conclusion : This study is the first to validate DAS28- squeeze using imaging techniques. From this study the false negative rate of DAS28-squeeze is lower thanDAS28. DAS28-squeeze has a better sensitivity and negative likelihood ratio than DAS28 in identifying RA disease state.Keywords : Rheumatoid Arthritis, DAS28, DAS28-squeeze, treat to target, Power Doppler, squeeze test